2015
DOI: 10.1097/mca.0000000000000223
|View full text |Cite
|
Sign up to set email alerts
|

Relation of red cell distribution width to contrast-induced acute kidney injury in patients undergoing a primary percutaneous coronary intervention

Abstract: Red blood cell distribution width, an inexpensive and easily measurable laboratory variable, is associated independently with the development of CI-AKI. Our data suggest that RDW may be a useful marker in CI-AKI risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 32 publications
7
37
0
1
Order By: Relevance
“…performed a cross-sectional study of 630 patients with ST-segment-elevation myocardial infarction who underwent primary percutaneous coronary intervention and concluded that RDW was an independent predictor of CI-AKI (OR=1.406, 95% CI 1.120 to 1.792), based on the multivariate logistic regression results [16]. A similar conclusion was reached in another study [17]. Nevertheless, to the best of our knowledge, this is the first study to investigate the relationship between RDW and AKI in patients in the CCU.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…performed a cross-sectional study of 630 patients with ST-segment-elevation myocardial infarction who underwent primary percutaneous coronary intervention and concluded that RDW was an independent predictor of CI-AKI (OR=1.406, 95% CI 1.120 to 1.792), based on the multivariate logistic regression results [16]. A similar conclusion was reached in another study [17]. Nevertheless, to the best of our knowledge, this is the first study to investigate the relationship between RDW and AKI in patients in the CCU.…”
Section: Discussionsupporting
confidence: 55%
“…Clinical trials have demonstrated that RDW has prognostic value in patients with chronic kidney disease [9], patients receiving hemodialysis or peritoneal dialysis [10-14] and patients with AKI who are being treated with continuous renal replacement therapy [15]. Moreover, a limited study found a connection between RDW and contrast-induced AKI (CI-AKI) in patients with ST-segment-elevation myocardial infarction who underwent primary percutaneous coronary intervention [16, 17]. In addition, to our knowledge, no study has investigated the association between RDW and the risk of AKI in critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…Kurtul A et al showed that increased RDW on admission is independently associated with a greater risk of CIN in patients undergoing PCI for acute coronary syndrome [17]. In another paper just published online, Akin F et al showed that preprocedural RDW was an independent predictor of patients with CIN who underwent primary PCI [18]. Although the association between RDW and several cardiovascular diseases is well known, its relation with CIN in SAP patients undergoing PCI remains unclear.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 96%
“…In this issue of Coronary Artery Disease, Akin and colleagues [11] add to the growing body of evidence that high RDW is another useful indicator of poor outcomes for patients after PCI. Their study finds that RDW is associated independently with the development of CI-AKI in STEMI patients after primary PCI.…”
mentioning
confidence: 94%